History, expectations, and public policy: Economic development in Eastern Germany - Andreas Schäfer; Thomas M. Steger (Center for Economic Studies and ifo Institute (CESifo), 2010)
Motivated by the process of economic development in Eastern Germany since the German reunification we set up a dynamic macroeconomic model of a small open economy where both capital and labor are mobile and there are increasing returns to scale at the aggregate level. The model features multiple equilibria as well as (local and global) indeterminacy. Expectations matter for resulting equilibrium dynamics, implying that economic confidence may be crucial for the process of economic development. Despite its simplicity, the model can replicate major empirical facts and bears a number of non-trivial implications.
Keywords: E60; H20; O40; 330; increasing returns to scale; capital mobility; migration; multiple equilibria; indeterminacy; history vs. expectations; economic policy; Wirtschaftliche Anpassung; Kleines-offenes-Land; Skalenertrag; Kapitalmobilität; Regionale Arbeitsmobilität; Regionale Entwicklung; Gleichgewicht; Wirtschaftspolitik; Vertrauen; Neue Bundesländer